Debridement and implant retention in the management of hip periprosthetic joint infection: outcomes following guided and rapid treatment at a single centre. (March 2017) - Sendi, P.; Lötscher, P. O.; Kessler, B.; Graber, P.; Zimmerli, W.; Clauss, M.
Abstract : Aims: To analyse the effectiveness of debridement and implant retention (DAIR) in patients with hip periprosthetic joint infection (PJI) and the relationship to patient characteristics. The outcome was evaluated in hips with confirmed PJI and a follow-up of not less than two years. Patients and Methods: Patients in whom DAIR was performed were identified from our hip arthroplasty register (between 2004 and 2013). Adherence to criteria for DAIR was assessed according to a previously published algorithm. Results: DAIR was performed as part of a curative procedure in 46 hips in 42 patients. The mean age was 73.2 years (44.6 to 87.7), including 20 women and 22 men. In 34 hips in 32 patients (73.9%), PJI was confirmed. In 12 hips, the criteria for PJI were not fulfilled and antibiotics stopped. In 41 (89.1%) of all hips and in 32 (94.1%) of the confirmed PJIs, all criteria for DAIR were fulfilled. In patients with exogenous PJI, DAIR was performed not more than three days after referral. In haematogenous infections, the duration of symptoms did not exceed 21 days. In 28 hips, a single debridement and in six hips two surgical debridements were required. In 28 (87.5%) of 32 patients, the total treatment duration was three months. Failure was noted in three hips (9%). Long-term follow-up results (mean 4.0 years, 1.4 to 10) were available in 30 of 34 (88.2%) confirmed PJIs. The overall successful outcome rate was 91% in 34 hips, and 90% in 30 hips with long-term follow-up results. Conclusion: Prompt surgical treatment with DAIR, following strict diagnostic and therapeutic criteria, in patients with suspected periprosthetic joint infection, can lead to high rates of success in eradicating the infection. Cite this article: Bone Joint J 2017;99-B:330–6.